2020
DOI: 10.1186/s13054-020-03352-0
|View full text |Cite
|
Sign up to set email alerts
|

Breath-synchronized electrical stimulation of the expiratory muscles in mechanically ventilated patients: a randomized controlled feasibility study and pooled analysis

Abstract: Background Expiratory muscle weakness leads to difficult ventilator weaning. Maintaining their activity with functional electrical stimulation (FES) may improve outcome. We studied feasibility of breath-synchronized expiratory population muscle FES in a mixed ICU population (“Holland study”) and pooled data with our previous work (“Australian study”) to estimate potential clinical effects in a larger group. Methods Holland: Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…El paciente con destete exitoso de la ventilación mecánica invasiva fue mayor en la asistencia ventilatoria con ajuste neural, la asistencia ventilatoria mecánica ajustada neuronalmente (NAVA) disminuye el tiempo del weaning dificultoso, así el SmartCare un modo con destete automático, ha demostrado disminuir las asincronías con el ventilador mecánico, por lo que, debería ser tomado en consideración en pacientes con weaning dificultoso (23). Los resultados obtenidos de un ensayo multicéntrico aleatorizado, realizado en pacientes mayores de 18 años, la neuroestimulación, para tratar la disfunción diafragmática, patología asociada a la ventilación mecánica prolongada, no ha demostrado buenos resultados (24), así como tampoco la estimulación eléctrica sincronizada ha demostrado diferencia significativa (25). La insuficiencia diafragmática durante el weaning dificultoso y la debilidad de los músculos respiratorios que se desarrolla con frecuencia en pacientes en estado crítico, se asocian con un resultado adverso durante la desconexión de la ventilación mecánica (26).…”
Section: Resultsunclassified
“…El paciente con destete exitoso de la ventilación mecánica invasiva fue mayor en la asistencia ventilatoria con ajuste neural, la asistencia ventilatoria mecánica ajustada neuronalmente (NAVA) disminuye el tiempo del weaning dificultoso, así el SmartCare un modo con destete automático, ha demostrado disminuir las asincronías con el ventilador mecánico, por lo que, debería ser tomado en consideración en pacientes con weaning dificultoso (23). Los resultados obtenidos de un ensayo multicéntrico aleatorizado, realizado en pacientes mayores de 18 años, la neuroestimulación, para tratar la disfunción diafragmática, patología asociada a la ventilación mecánica prolongada, no ha demostrado buenos resultados (24), así como tampoco la estimulación eléctrica sincronizada ha demostrado diferencia significativa (25). La insuficiencia diafragmática durante el weaning dificultoso y la debilidad de los músculos respiratorios que se desarrolla con frecuencia en pacientes en estado crítico, se asocian con un resultado adverso durante la desconexión de la ventilación mecánica (26).…”
Section: Resultsunclassified
“…There have been other clinical risk predictive models used to assist with decision-making [ 7 , 15 17 ], but the CRI offers several advantages. The variables are objective and easily obtained at the time of presentation, and the scoring system is simple.…”
Section: Discussionmentioning
confidence: 99%
“…Titin loss may be an important cause of other respiratory muscle dysfunctions as well as that of the diaphragm. Jonkman et al reported that breath-synchronized electrical stimulation increased the thickness of abdominal expiratory muscles (1.76 mm vs. −0.50 mm in intervention vs. control, p = 0.02) [45]. Thus, titin loss may be reversible by active rehabilitation.…”
Section: Other Respiratory Muscle Atrophymentioning
confidence: 99%